Entrepreneurial orientation and external technology acquisition: an empirical test on performance of technology-based new ventures - Cai, Li; Liu, Qing; Deng, Shengliang; Cao, Dan (Journal of Business Economics and Management, 2014)
This research investigates the effects of entrepreneurial orientation and external technology acquisition on the performance of technology-based new ventures in the context of a transitional economy. An analysis of the cross-sectional data from 123 Chinese technology-based new ventures was conducted. The results of the analysis support the contention that both the acquisition of external technology and entrepreneurial orientation improve new ventures’ performance. Additionally, the interaction of entrepreneurial orientation and external technology acquisition positively moderates the relationship between entrepreneurial orientation and performance of technology-based new ventures. Overall, this study contributes to our enhanced understanding of the complex relationship among entrepreneurial orientation, external technology acquisition and firm performance under transitional economic conditions. Firms from emerging economies, especially technologybased new ventures, may find the study findings useful in guiding their decision on external technology acquisition.